2018
DOI: 10.1016/j.wear.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Concrete-ice abrasion: Wear, coefficient of friction and ice consumption

Abstract: Concrete structures in the Arctic offshore are often exposed to drifting ice causing abrasion of concrete surfaces. This paper presents the results of a laboratory study of concrete-ice abrasion. The sawn concrete surfaces (two high-performance concrete mixes and one light weight mix of concrete) were exposed to sliding freshwater ice under 1 MPa pressure for 3 km of sliding distance. The effect of concrete compressive strength, ice consumption, and the coefficient of friction on abrasion was studied simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…An earlier part of this study found that the abrasion of high-performance concrete after 3 km of effective sliding distance was in the order of 0.1 mm, and the majority of the surface damage was observed during the first sliding kilometre [15]. This was interpreted as severe abrasion of concrete during the running-in process of sliding experiments from 0 to 1 kilometre, which was followed by mild wear (steady state) over the distance from 1 to 3 kilometres, where abrasion rates were much smaller [15]. The difference in abrasion rates could not be explained by the coefficient of friction (COF).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…An earlier part of this study found that the abrasion of high-performance concrete after 3 km of effective sliding distance was in the order of 0.1 mm, and the majority of the surface damage was observed during the first sliding kilometre [15]. This was interpreted as severe abrasion of concrete during the running-in process of sliding experiments from 0 to 1 kilometre, which was followed by mild wear (steady state) over the distance from 1 to 3 kilometres, where abrasion rates were much smaller [15]. The difference in abrasion rates could not be explained by the coefficient of friction (COF).…”
Section: Introductionmentioning
confidence: 69%
“…In these experiments, the concrete surface is abraded by fresh-water ice produced by unidirectional freezing. The density of the ice is 917.0 kg/m 3 , so its porosity is very low: 0.1 -0.0033% [15]. The method of ice production is described in detail in our previous paper [26].…”
Section: Concrete Mixes and Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical laws exist for the other three types of erosion (e.g., [17][18][19][20][21][22][23][24][25][26]). A mechanistic erosion law for valley glacier was proposed in Reference [27], to consider a combination of frictional abrasion and glacier quarrying.…”
Section: Erosion Lawsmentioning
confidence: 99%
“…With the extension of the service time of the concrete, durability decreases, which leads to the destruction of the concrete structure [4,5]. Owing to the different environments in which concrete is used, there are many types of concrete damage, which can be roughly divided into the following: steel corrosion, freeze-thaw damage, chemical erosion, structural cracking [6,7], and abrasion damage (ground wear, erosion wear) [8][9][10]. Studies have shown that moisture has a direct or indirect effect on concrete damage.…”
Section: Introductionmentioning
confidence: 99%